Implementation of Education Game-Based Learning Media Kahoot! In Agribisnis at the University Of Bangka Belitung - Zaliman, Iski; Juniawan, Fransiskus Panca; Wafiqoh, Risnina; Heryati, Agustina; Andini, Dwi Yana Ayu; Sylfania, Dwi Yuny; Vista, Umar Faruq (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Education is a process of changing knowledge, increasing, skills, improving attitudes and behavior of humans or groups that are trying to educate the life of the nation and humans by carrying out learning and teaching process activities as well as guidance on training learning. Among the developments in science and technology (science technology), technology applications to websites are now widely available and can facilitate the student learning process in an interactive and active way, with the application of this technology it provides opportunities for students to review information and be able to practice knowledge, as well as student skills in the learning process by enjoying the game.